Overcoming powdery mildew in cashew - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Tanzania was the world's second biggest producer of cashew nuts in the mid-1970s, but production plummeted during the late 70s and early 80s. By the late 80s production was only a tenth of what it had been at its peak. Investigation during this...